2013
DOI: 10.1177/193229681300700115
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Self-Titration of Oral Glucose-Lowering Medication Using a Mobile Telephone-Based Telehealth Platform in Type 2 Diabetes: A Feasibility Trial in Primary Care

Abstract: Abbreviations: (CI) confidence interval, (HbA1c) hemoglobin A1c, (IQR) interquartile range, (NICE) National Institute for Health and Clinical Excellence, (SD) standard deviation, (SMBG) self-monitored blood glucose Keywords: oral glucose-lowering medication, self-monitoring of blood glucose, self-titration, telehealth, type 2 diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…164,166,168,171,178 We also include in Table 5 a systematic review by Liang et al 173 and a Cochrane review. 174 The systematic review included 22 trials.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…164,166,168,171,178 We also include in Table 5 a systematic review by Liang et al 173 and a Cochrane review. 174 The systematic review included 22 trials.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…We found that~30% of participants reported self-titrating, which may indicate a potential opportunity for self-focused interventions to improve dosing [36,37]. We found that~30% of participants reported self-titrating, which may indicate a potential opportunity for self-focused interventions to improve dosing [36,37].…”
Section: Discussionmentioning
confidence: 71%
“…Nagrebetsky et al. investigated telehealth system with real‐time graphical feedback and remote nurse monitoring through mobile phones for adjusting the dose of oral hypoglycaemic agents in type 2 diabetic patients. The study concluded with a significant decrease in the HbA1c levels.…”
Section: Resultsmentioning
confidence: 99%
“…The selection criteria was original articles that reported clinical studies evaluating mobile apps in diabetes patients. These studies were reported from several countries including France , UK , Italy , Canada , USA , South Korea , Taiwan , Norway , Australia and Austria . Patients were recruited from primary and tertiary hospitals and community settings.…”
Section: Methodsmentioning
confidence: 99%